TRH and TRH receptor system in the basolateral amygdala mediate stress-induced depression-like behaviors. (October 2015) - Choi, Juli; Kim, Ji-eun; Kim, Tae-Kyung; Park, Jin-Young; Lee, Jung-Eun; Kim, Hannah; Lee, Eun-Hwa; Han, Pyung-Lim
Abstract: Chronic stress is a potent risk factor for depression, but the mechanism by which stress causes depression is not fully understood. To investigate the molecular mechanism underlying stress-induced depression, C57BL/6 inbred mice were treated with repeated restraint to induce lasting depressive behavioral changes. Behavioral states of individual animals were evaluated using the forced swim test, which measures psychomotor withdrawals, and the U-field test, which measures sociability. From these behavioral analyses, individual mice that showed depression-like behaviors in both psychomotor withdrawal and sociability tests, and individuals that showed a resiliency to stress-induced depression in both tests were selected. Among the neuropeptides expressed in the amygdala, thyrotropin-releasing hormone (TRH) was identified as being persistently up-regulated in the basolateral amygdala (BLA) in individuals exhibiting severe depressive behaviors in the two behavior tests, but not in individuals displaying a stress resiliency. Activation of TRH receptors by local injection of TRH in the BLA in normal mice produced depressive behaviors, mimicking chronic stress effects, whereas siRNA-mediated suppression of either TRH or TRHR1 in the BLA completely blocked stress-induced depressive symptoms. The TRHR1 agonist, taltirelin, injection in the BLA increased the level of p-ERK, which mimicked the increased p-ERK level in the BLA that was induced by treatment with repeated stress. Stereotaxic injection of U0126, a potent inhibitor of the ERK pathway, within the BLA blocked stress-induced behavioral depression. These results suggest that repeated stress produces lasting depression-like behaviors via the up-regulation of TRH and TRH receptors in the BLA.